Prevalence of Bacterial Uropathogens Among Diabetic Patients Attending Padma Nursing Hospital of Western Nepal - Tamang, Kamal; Shrestha, Pashupati; Koirala, Amrit; Khadka, Jagat; Gautam, Narayan; Rijal, Komal Raj (Himalayan Journal of Science and Technology, 2017)
Urinary tract infections (UTIs) are common in patients with diabetes mellitus (DM). The propensity of the infection can vary in different individuals especially when there is underreporting from the patients having a risk of acquiring infections. This study was conducted in Padma Nursing Home, Pokhara, Nepal from April to September, 2014. A total of 200 mid-stream urine samples were collected from diabetic patients visiting the nursing home and processed by standard laboratory procedure. Antibiotic susceptibility test was performed by modified Kirby-Bauer disk diffusion method. About 13% of the patient’s urine specimens had shown UTIs. The prevalence of UTI was 18.1% in female and 8.5% in male. Statistically significant association of UTI was found with gender and pyuria. E. coli was the most predominating organism (37%) causing UTI followed by Enterococcus spp (22.2%) and Klebsiella spp. (14.8%). Nitrofurantoin and Ciprofloxacin were the most potent drugs. UTIs are more frequent and are likely to have a more complicated course in patients with DM. This study pointed out that higher age patients, female gender and diabetic patients are risk groups for UTI and should be very cautious to so as to prevent it.